2017
DOI: 10.1017/s1751731116002202
|View full text |Cite
|
Sign up to set email alerts
|

Review: Drinking water for liquid-fed pigs

Abstract: Liquid feeding has the potential to provide pigs with sufficient water to remain hydrated and prevent prolonged thirst. However, lack of permanent access to fresh water prevents animals from drinking when they are thirsty. Moreover, individual differences between pigs in a pen may result in uneven distribution of the water provided by the liquid feed, leading to some pigs being unable to meet their water requirements. In this review, we look at the need for and provision of water for liquid-fed pigs in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…As evidenced in the study reported here, liquid feeding during the early weaning period improves FI and BWG, which were in line with other reports in the literature (Kim et al, 2001;Price et al, 2013). The beneficial effects of liquid feeding on the FI and BWG of weanling pigs might be associated with provision of most of the pig' food and water requirements within a single source, thus eliminating the need to learn separate feeding and drinking behaviors (Meunier-Salaün et al, 2017). In addition, previous studies have indicated that management strategies that increased the water consumptions of young pigs resulted in improved growth (Gill et al, 1987) and prevented dehydration (Russell et al, 1996).…”
Section: Growth Performancesupporting
confidence: 92%
“…As evidenced in the study reported here, liquid feeding during the early weaning period improves FI and BWG, which were in line with other reports in the literature (Kim et al, 2001;Price et al, 2013). The beneficial effects of liquid feeding on the FI and BWG of weanling pigs might be associated with provision of most of the pig' food and water requirements within a single source, thus eliminating the need to learn separate feeding and drinking behaviors (Meunier-Salaün et al, 2017). In addition, previous studies have indicated that management strategies that increased the water consumptions of young pigs resulted in improved growth (Gill et al, 1987) and prevented dehydration (Russell et al, 1996).…”
Section: Growth Performancesupporting
confidence: 92%
“…Possible reasons for the improvement in growth performance of fermented liquid feeding are as follows: (1) Fermented liquid feeding can increase the content of small peptides (such as acid-soluble protein [ 11 ]) and decrease the content of antinutritional factors, increasing the palatability and digestibility of feed [ 27 ]. (2) Fermented liquid feeding can effectively solve the problem of insufficient drinking water caused by competition among pigs and promote growth performance [ 28 ]. However, no effect on the ratio of feed to gain was observed in this experiment among the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…or perhaps a combination of both may be involved [ 6 ]. Liquid feed diets have been widely used in western and southern Europe for 20 years, especially in France and Italy [ 7 ]. There has been an increase in the use of fermented liquid and liquid feed in the European Union (EU) since the ban on the use of antibiotics as growth promoters in pig feed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%